Factors that influence the youths’ involvement in Malaysian politics / Nur Asma Noor Affendy and Nur Sabrina Sarah Zakaria - Noor Affendy, Nur Asma; Zakaria, Nur Sabrina Sarah (2022)
Malaysian Youths are criticized for their lack of interest in politics. This is due to the fact that they represent a large number of unregistered voters. Therefore, this paper provides three factors that influence them to be involved in politics. For this purpose, a survey is conducted on 341 undergraduates’ UiTM Seremban 3 students in the Faculty of Administrative Science and Policy Studies. Three independents variable have been used in this study including the social media, political knowledge, and family background. The hypotheses were tested by using the Pearson Correlation test from the SPSS. The result shows that all the variables are correlated to the (social media: r = 0.510, p = .000), (political knowledge: r= 0.423, p = .000) and the (family background: r = 0.449, p = .000).